FOUNDATIONS OF NEUROMARKETING STRATEGY IN INDUSTRY - Boltaeva, Zinora (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The purpose of the study examination for the theoretical foundations of such a relatively new branch of behavioral economics as neuromarketing. The paper discusses the main methods and tools of neuromarketing. In addition, the article provides a brief description of the possibilities of its application in modern realities.